Awareness of cash waqf among students of Diploma in Muamalat and Diploma in Halal Management of UiTM Puncak Alam, Selangor / Nursyaza Aqilah Shamsuri - Shamsuri, Nursyaza Aqilah (Academy of Contemporary Islamic Studies (ACIS), 2018)
The perception of the community has been synonymous with assuming that waqf only consists of a property that is permanent and durable. Cash waqf is a trust fund comprising the fees received by the community and is one of the alternative instruments in eradicating poverty among Muslims. However, the existence of cash waqf is still a question mark by most individuals. In this regard, this study will see how far the student's knowledge of the concept of cash waqf gives awareness to the public to implement the cash wakaf. The study was conducted based on primary data interviewed by several ACIS students, at UiTM Kampus Puncak Alam, Selangor. The findings reveal that knowledge is significant and relates positively in giving awareness and understanding of cash waqf. Although the Islamic community of UiTM students of Puncak Alam Campus is aware and understand about cash waqf, the majority still do not engage in the cash wakaf. This study is expected to help the parties, especially the responsible parties in raising the awareness of the local community, especially the young in order to increase the involvement in the cash waqf activities that can be accompanied by all levels of society.